A strategy and detailed explanations to the composites of Si/MWCNTs for lithium storage. (January 2021) - Xu, Ruhui; Wei, Runhong; Hu, Xuejun; Li, Yin; Wang, Li; Zhang, Keyu; Wang, Yunke; Zhang, Hui; Liang, Feng; Yao, Yaochun
Abstract: Nano-Si/MWCNTs composite was a representative solution to improve Si-based anode material's rate performance in lithium-ion batteries (LIBs). However, the problems of easy agglomeration of silicon nanoparticles and carbon nanotubes hindered Si/MWCNT's further development. In this study, we combine silicon nanoparticles with MWCNTs cleverly by utilizing freeze-drying method to solve the problems and enhance silicon-based material's rate performance. Compared with Si-MWCNTs composite treated by electric blast-drying method, the rate performance of Si-MWCNTs treated by freeze-drying is significantly improved, especially at different current densities. When Si-MWCNTs are encapsulated in FPC (flour-derived porous carbon, FPC), the as-obtained Si-MWCNTs-PVPC-FPC-SC-1 (sucrose-derived carbon, SC) prepared by freeze-drying method delivers a reversible capacity of 1347.5 mAh g −1 at 0.1 A g −1 after cycling at 5 A g −1 and a reversible capacity of 501 mAh g −1 at 1 A g −1 after 500 cycles. Our study demonstrates that the freeze-drying method can solve the problems of easy agglomeration of silicon nanoparticles and MWCNTs as well as improve Si-based anode's rate performance for LIBs. The synthetic route presented in this paper is low-cost and easy to scale up for silicon-carbon (Si/C) composites with high rate performance and long cycle life. Graphical abstract: Image 1 Highlights: Freeze-drying method is used to combine Si with MWCNTs to enhance Si-based material's rate performance. We analyzed the reason why freeze drying brought beneficial effects on Si-MWCNTs composites. Precursor treated by freeze-drying method was encapsulated into porous carbon to enhance material's high rate performance. The 500th reversible capacity of Si-MWCNTs-PVPC-FPC-SC-1 reaches 501 mAh g −1 at 1 A g −1 .